Application of Text Mining to Visualize the Fluctuation of Food Commodity Prices (Case Study Twitter, Liputan6, Detik)) - Rakha Beavis Luckyano (Jurnal Sistem Informasi Universitas Dinamika, 2022)
The fluctuation of food commodity prices will be worsened as the after effect of the global warming. Nowadays, to collect food commodity price, we could search the unstructured data on the online news sites or social media sites which still going to take a lot of time to manually process. This research aim to build a desktop application which will implement text mining technique and jaro-winkler algorithm to process the data received from the source and visualized it on line diagram. Based on the accuracy testing result, the application recieved 75% accuracy